Benzathine penicillin G: a model for long‐term pharmacokinetic comparison of parenteral long‐acting formulations. (7th January 2013) - Shahbazi, M. A.; Azimi, K.; Hamidi, M.
Summary What is known and Objective: Long‐acting intramuscular penicillin G injection is an important product for the management of some severe infections. However, testing the bioequivalence of such long‐acting formulations is difficult. Our aim was to undertake such a test using a generic formulation containing 1 200 000 IU of benzathine penicillin G powder and an innovator's product (Retarpen® 1·2 million units; Sandoz, Switzerland). Methods: In an open, double‐blind, randomized, two‐periods, two‐group crossover study, 12 healthy male volunteers received both formulations of benzathine penicillin G on two different days with a 5‐month washout period between the doses and a sampling period of over 500 h. A simple, sensitive and rapid high‐performance liquid chromatography (HPLC)‐UV method was developed and validated for determination of penicillin G plasma concentrations and other pharmacokinetic (PK) parameters. Results and Discussion: The analytical method used produced linear responses within a wide analyte concentration range with average within‐run and between‐run variations of below 15% with acceptable recovery, accuracy and sensitivity. The primary PK parameters we used were maximum plasma concentration (Cmax), time to reach the maximal concentration (Tmax) and the area under the plasma concentration vs. time curve from time zero to the last sampling time (AUC0→t) using a standard non‐compartmental approach. Based on these parameters, the two formulations were bioequivalent. What is new and Conclusion: We illustrate the bioequivalence testing of a very long‐acting product. The data indicate that the generic test formulation and the branded reference formulation were bioequivalent in fasting healthy Iranian male volunteers.